Worldspace, satellite network to link radio to the Internet - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Arid Lands Information Network - Eastern Africa (ALIN-EA) has joined up with the US digital broadcast pioneer WorldSpace Foundation to get online information to remote rural areas using digital satellite broadcasting.